Analyzing Factors Enabling Colorectal Cancer Screening Adherence in Korean Americans Using the Andersen’s Behavioral Model of Health Services Utilization - Jin, Seok Won (J Psychosoc Oncol, 2019)
PURPOSE/OBJECTIVES: Korean Americans (KAs) report suboptimal colorectal cancer (CRC) screening adherence. This study investigated factors that enable KAs to adhere to CRC screening guidelines using Andersen’s Behavioral Model of Health Services Utilization. DESIGN: Cross-sectional survey using self-report measures of CRC screening behaviors. SAMPLE AND METHODS: Purposive sampling was used to recruit 433 KAs aged 50–75 from the Atlanta metropolitan area who completed questionnaires measuring predisposing (i.e., gender, age, marital status, educational attainment), enabling (income, health insurance, regular annual check-ups, doctor recommendation, English proficiency, CRC knowledge, self-efficacy for CRC screening, decisional balance in CRC screening), and need (family cancer history, self-reported health status) factors associated with CRC screening. FINDINGS: A multiple logistic regression model including all 14 predictor variables revealed that several enabling factors (i.e., income, regular annual health check-ups, doctor’s recommendation, self-efficacy, and decisional balance) independently predicted increased CRC screening adherence in KAs. No predisposing or need factors independently predicted CRC screening. CONCLUSIONS AND IMPLICATIONS FOR PSYCHOSOCIAL PROVIDERS OR POLICY: To increase CRC screening adherence among KAs, psychosocial interventions should target on improving their self-efficacy and decisional balance regarding CRC screening, while policy interventions should focus on promoting health providers’ CRC screening recommendations during routine health check-ups.